DOING MATHEMATICS INTELLIGENTLY AND HAVING GOOD CHARACTER THROUGH SIMPATIK LEARNING - Euis Eti Rohaeti; Heris Hendriana; Muhammad Irfan (Jurnal Infinity, 2023)
Society’s openness to science, technology, and information development cannot be stopped. To face the development of technology and information, we must be intelligent in assessing, accommodating, and filtering the development of technology and information so that we can survive in constantly changing, uncertain, and competitive conditions. Besides intelligence, the character is also important to face the development of science, technology, and information. Individuals who have good character will be wiser in utilizing the development of science, technology, and information. Therefore, in this analytical research paper, we introduce SIMPATIK learning to increase the effectiveness of learning mathematics at school. Through SIMPATIK learning, students can do mathematics intelligently and have good character. SIMPATIK learning can be defined as learning that can develop sociocultural, innovative, independent, caring, creative, and active abilities in mathematics learning based on information, communication, and technology. We believe that SIMPATIK Learning can increase the quality of mathematics learning and can be used by teachers to develop the intelligence and character of students. SIMPATIK Learning is also expected to contribute science to knowledge in mathematics education worldwide.